MENGEMBANGKAN SIKAP GOTONG ROYONG MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) BERMUATAN KEARIFAN LOKAL - Zulfa Nurul Ain; Ani Siti Anisah; Ade Holis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education plays a significant role in shaping the personalities of young generations in alignment with the values of Pancasila. An innovative change designed to support this is the implementation of the Project to Strengthen the Profile of Pancasila Students (P5), which incorporates local wisdom. This study aims to describe the development of cooperative attitudes among students through P5 based on local wisdom at SDIT Atikah Musadad, Garut. The method used is a descriptive qualitative approach, where data is collected through interviews, observations, and documentation. The data analysis process is conducted in several stages, including data collection, data reduction, data display, and conclusion drawing/verification. This study found that implementing P5 significantly improved students' cooperative attitudes, as evidenced by the "Highly Developed" category increase from 0% before P5 to 84% afterward. Group activities such as batik dyeing and local culture appreciation campaigns have made a tangible contribution to fostering values of teamwork, care, and togetherness. Based on the research findings, the integration of cooperative values in P5 with local wisdom has proven effective in developing student attitudes that align with the Profile of Pancasila Students, particularly in the dimension of cooperation.